Topographic Map Making for Students of SMK Kehutanan, Pekanbaru: Pembuatan Peta Topografi bagi Siswa SMK Kehutanan Pekanbaru - Muhammad Ikhwan; Ikhsani, Hanifah; Emy Sadjati (Universitas Lancang Kuning, 2024)
Topographic maps have several benefits, such as providing a basis for regional planning and identifying the vulnerability and hazards of an area. Therefore, making topographic maps is important for forestry students, especially using drone data. The purpose of the service is to increase the partners' knowledge about the use of drones for topographic mapping and basic knowledge about drone operation, and to improve the partners' skills by providing training in making topographic maps from data collected by drones. The activities carried out include providing materials on topographic map making and basic knowledge on drone operation. Furthermore, the practice of topographic map making and evaluation activities. There is an average increase of 25.52% in the partners' knowledge. The partners already have the skills to produce topographic maps. It's just that further training on map layout material is needed to maximize the topographic maps produced by partners.